The Ex-Husband - Hamilton, Karen (Karen J.) (Thorndike, Maine : Center Point Large Print, 2022)
"Charlotte has an unsavory past, but shes on the straight and narrow these days. She was so young then - she married the wrong man, falling for Sams sweet-talking charm and charisma, and got caught up in his con-artist games. If only shed left him before things went too far. Now Sam is missing. But before he disappeared, he left urgent, cryptic messages about someone threatening him - someone who has been threatening Charlotte, too. So Charlotte takes a job as a personal assistant for an engagement party aboard a private luxury cruise ship, the Cleobella, to get far away from anyone who means her harm. But as the Cleobella sails through its glittering destinations, increasingly sinister events haunt the guests, and the turquoise waves and sun-drenched beaches give way to something darker. Someone knows what Charlotte did. Is it the blushing bride? The seemingly placid mother-in-law? Or the mysterious heiress? Someone knows, and someone wants revenge - before the ship reaches its final port."--
Keywords: Missing persons -- Fiction; Divorced people -- Fiction; Revenge -- Fiction; Family secrets -- Fiction; Detective and mystery fiction; Thrillers (Fiction)